2016
DOI: 10.1159/000442664
|View full text |Cite
|
Sign up to set email alerts
|

Appendiceal Adenocarcinoma Presenting as a Rectal Polyp

Abstract: Appendiceal adenocarcinoma typically presents as an incidentally noted appendiceal mass, or with symptoms of right lower quadrant pain that can mimic appendicitis, but local involvement of adjacent organs is uncommon, particularly as the presenting sign. We report on a case of a primary appendiceal cancer initially diagnosed as a rectal polyp based on its appearance in the rectal lumen. The management of the patient was in keeping with standard practice for a rectal polyp, and the diagnosis of appendiceal aden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 8 publications
(9 reference statements)
0
3
0
Order By: Relevance
“…Previous studies have reported that preoperative imaging techniques are ineffective in accurately exhibiting the origin and extent of appendiceal adenocarcinoma [ 1 ], often necessitating surgical intervention for diagnostic and therapeutic purposes [ 1 , 2 , 6 ]. Here, we demonstrate that preoperative staging MRI was, in fact, crucial in identifying the appendiceal origin of this carcinoma and its invasion to the urinary bladder and rectum.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have reported that preoperative imaging techniques are ineffective in accurately exhibiting the origin and extent of appendiceal adenocarcinoma [ 1 ], often necessitating surgical intervention for diagnostic and therapeutic purposes [ 1 , 2 , 6 ]. Here, we demonstrate that preoperative staging MRI was, in fact, crucial in identifying the appendiceal origin of this carcinoma and its invasion to the urinary bladder and rectum.…”
Section: Discussionmentioning
confidence: 99%
“…Although right lower quadrant abdominal pain mimicking acute appendicitis is more commonly seen as the primary presenting symptom [ 2 ], irritative urinary symptoms such as increased frequency, dysuria [ 1 , 4 ], hematuria, and fecaluria can occur [ 5 ]. The prognosis depends on the extent of organ invasion and spread of the tumor in the peritoneal cavity, as well as the type of surgery performed [ 6 ]. The preoperative determination of the origin and extent of appendiceal carcinoma is challenging [ 1 ].…”
Section: Introductionmentioning
confidence: 99%
“…Prognosis is also worse among patients presenting with appendiceal malignancy. One of the reasons for this is related to the higher propensity of appendiceal cancer to spread through the lymphatic system [12].…”
Section: Discussionmentioning
confidence: 99%